The effectiveness of I-Staff Portal to the staff of UiTM Dungun / Nurul Hafiza Mat Ali ... [et al.] - Mat Ali, Nurul Hafiza; Ismail, Norhasimah; Khalib, Nurul Humairah; Mohamud, Siti Azura (2009)
This report is all about the effectiveness of I-Staff Portal to the staff of UiTM Dungun. The words portal can refer to a single, personalized interface through which users access all information resources and services in a secure, consistent and customizable manner. There are one problem statement that are identified which is the researcher of this study feels that the availability of I-Staffportal for use by UiTM staff has not been fully realized. So, this study seeks to investigate the level of usage of this portal and whether its usage has eventually lead to a more effective delivery of service to customers. Objective of the research is to find out the factors contributing towards the effective use of I-Staff Portal, to analyze the frequency of use of the I- Staff Portal by UiTM staff and also to identify the effects of I-Staff Portal on staffperformance.